Comparative impact of supine vs prone positioning on dose distribution, acute toxicity, and setup error in postoperative radiotherapy for cervical cancer: a multidimensional propensity-matched cohort study - Xiao, Nanjie; Yuan, Cuiyun; Zhao, Tianshu; Xu, Tie; Zhou, Jiaomei; Liao, Junfang; Peng, Miao; Liu, Chenbin; Chen, Zhijian; Jin, Jing (Frontiers in Oncology, 2025)
BackgroundPostoperative radiotherapy is standard for high-risk cervical cancer, but acute toxicities—particularly gastrointestinal and hematologic—remain clinically relevant. Patient positioning may influence organ dose exposure and setup accuracy, yet its multidimensional clinical impact is poorly characterized.MethodsThis retrospective cohort study evaluated patients with cervical cancer treated with postoperative volumetric modulated arc therapy between 2019 and 2022. Propensity score matching (2:1) produced a balanced matched cohort of prone and supine treatments for comparative analyses. Primary endpoints included pelvic organ dose-volume parameters, interfractional setup error, and grade ≥2 hematologic and gastrointestinal toxicities, evaluated using multivariable logistic regression and linear mixed-effects models.ResultsIn this single-center retrospective cohort (n = 168), propensity score matching (2:1) yielded 112 balanced patients (prone n = 70; supine n = 42). After matching, target coverage was comparable between positions (PTV_D95: 45.52 Gy vs 45.54 Gy, p = 0.24). The prone group showed higher low-dose exposure in bowel bag and rectum at V5–V15 (e.g., V10 difference −9.84%, 95% CI −17.07 to 1.08; adjusted p = 0.040). Setup error was similar across all axes (p > 0.05). The supine group had significantly higher incidence of leukopenia (92.9% vs 71.4%; p = 0.0073), with prone positioning associated with reduced hematologic toxicity (OR = 14.40, 95% CI 1.60–129.74; p = 0.017). Conversely, diarrhea occurred more often in the prone group (44.3% vs 26.2%, p = 0.070), and supine positioning was protective in multivariable analysis (OR = 0.42, 95% CI 0.17–0.97; p = 0.047).ConclusionThese findings suggest prone positioning may be preferable for patients with limited hematopoietic reserve, while supine positioning may benefit those with gastrointestinal vulnerability. Positioning choice should be individualized based on toxicity risk and functional anatomy to optimize safety in postoperative cervical cancer radiotherapy.